A perspectiva docente sobre a inclusão de alunos com deficiência nas aulas de educação física, no contexto das transições ecológicas apae, ensino regular. - Koch, Lucas Luan Gonçalves. [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The study addresses the central issue of the challenges faced in the inclusion of students with disabilities in Physical Education classes, highlighting how this practice still presents significant difficulties in everyday school life. The investigation sought to understand, according to its original purpose, how teachers perceive this process and which benefits, strategies, and barriers are observed during these students’ participation in classes. To achieve this goal, a qualitative methodological approach was adopted, characteristic of exploratory research, aimed at an in-depth understanding of teachers’ experiences. This approach allowed for the capture of meanings and interpretations, without the intention of quantification, emphasizing the complexity of the human relationships involved. Five Physical Education teachers from the municipal school network of Arealva-SP participated in the study, selected through invitation and formal consent. Their experiences were recorded through data collection based on semi-structured interviews, organized around thematic axes related to professional profile, initial and continuing education, knowledge about ASD and ID, and perceptions regarding transitions between family, school, and APAE environments. The information gathered was analyzed through a content analysis process, following an interpretive procedure that includes stages of organization, exploration, and interpretation of the data. This analysis dialogued with the Bioecological Theory of Human Development, used as the theoretical framework to understand the influence of different environmental systems on student development and teaching practices. The main results indicate relevant gaps in teachers’ initial training, as they acknowledged not being fully prepared to work with students with disabilities upon completing their degrees. Although some had taken courses related to the topic, practical experiences were considered insufficient for the school context. Continuing education emerged as a fundamental component, especially regarding themes such as ASD, curricular adaptation, and inclusive pedagogical strategies. Among the obstacles reported, large class sizes, lack of specialized support, and the need for individualized planning stood out. Despite these challenges, teachers identified important benefits provided by Physical Education, including improvements in socialization, motor development, communication, organization, and cognitive aspects. It was also observed that students who simultaneously attend school and APAE show significant progress, reinforcing the importance of ecological transitions between different environments. In this sense, dialogue among family, school, and specialized institutions was identified as essential to ensuring continuity and coherence in student development. In summary, the research highlights that inclusion cannot be viewed as the sole responsibility of the teacher, but rather as a collective and systemic process that depends on public policies, adequate training, and articulation among educational contexts. Although challenges persist, the findings demonstrate that Physical Education has the potential to broadly support the development of students with disabilities, provided that structural conditions, institutional support, and continuous training are ensured.

O estudo aborda a questão central relacionada às dificuldades enfrentadas na inclusão de alunos com deficiência nas aulas de Educação Física, ressaltando como essa prática ainda apresenta desafios significativos no cotidiano escolar. A investigação buscou compreender, de acordo com sua finalidade original, como os professores percebem esse processo e quais benefícios, estratégias e entraves são observados durante a participação desses alunos nas aulas. Para atingir esse propósito, adotou-se um percurso metodológico qualitativo, característico de pesquisas exploratórias, voltado à compreensão aprofundada das experiências docentes. Tal abordagem permitiu captar sentidos e interpretações, sem intenção de quantificação, enfatizando a complexidade das relações humanas envolvidas. Participaram do estudo cinco professores de Educação Física da rede municipal de Arealva-SP, selecionados mediante convite e consentimento formal. Suas experiências foram registradas por meio de uma coleta baseada em entrevistas semiestruturadas, estruturadas em eixos temáticos referentes ao perfil profissional, formação inicial e continuada, conhecimento sobre TEA e DI e percepções sobre a transição entre os ambientes da família, escola e APAE. As informações obtidas foram examinadas por meio de um processo de análise de conteúdo, conforme um procedimento interpretativo que inclui etapas de organização, exploração e interpretação dos dados. Essa análise dialogou com a Teoria Bioecológica do Desenvolvimento Humano, utilizada como eixo teórico para compreender a influência dos diferentes sistemas ambientais sobre o desenvolvimento dos alunos e o trabalho docente. Os principais resultados apontam lacunas relevantes na formação inicial dos professores, que reconheceram não estar plenamente preparados para atuar com alunos com deficiência ao concluir a graduação. Embora alguns tenham cursado disciplinas relacionadas à temática, as experiências práticas foram consideradas insuficientes para a realidade escolar. A formação continuada emergiu como elemento fundamental, especialmente em temas como TEA, adaptação curricular e estratégias pedagógicas inclusivas. Entre os obstáculos relatados, destacaram-se as turmas numerosas, a ausência de apoio especializado e a necessidade de planejamento individualizado. Apesar disso, os professores identificaram ganhos importantes proporcionados pela Educação Física, incluindo melhorias na socialização, desenvolvimento motor, comunicação, organização e aspectos cognitivos. Observouse também que alunos que frequentam simultaneamente a escola e a APAE apresentam avanços significativos, reforçando a importância das transições ecológicas entre os diferentes espaços. Nesse sentido, o diálogo entre família, escola e instituição especializada foi apontado como essencial para garantir continuidade e coerência no desenvolvimento do estudante. Em síntese, a pesquisa evidencia que a inclusão não pode ser vista como responsabilidade isolada do professor, mas como um processo coletivo e sistêmico que depende tanto das políticas públicas quanto da formação adequada e da articulação entre os contextos educativos. Ainda que existam obstáculos, os dados demonstram que a Educação Física possui potencial para favorecer de maneira ampla o desenvolvimento de alunos com deficiência, desde que acompanhada de condições estruturais, apoio institucional e formação contínua.
The teacher's perspective on the inclusion of students with disabilities in physical education classes, in the context of ecological transitions apae, regular education.
Keywords: Inclusão; Deficiência; APAE; Educação Física; Inclusion; Disability